2000
DOI: 10.1111/j.1460-2466.2000.tb02844.x
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Determinants of International News Coverage: A Comparison of 38 Countries

Abstract: This study investigates the influence of systemic determinants on international news coverage in 38 countries. Systemic factors include traits of nations, magnitude of interaction and relatedness between nations, and logistics of news gathering.Multiple regression is implemented to assess 9 systemic determinants in each individual country. Findings indicate that the U.S. was the most covered country in the world. In spite of some variation, trade volume and presence of international news agencies were found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
232
3
15

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 311 publications
(268 citation statements)
references
References 18 publications
18
232
3
15
Order By: Relevance
“…This imbalance in the global exchange of news means, in the words of Jaap van Ginneken (1998), "the perspectives of the great mass of the world population are under-represented in global news, while those of relatively small élites are overrepresented" (p. 143). This tendency creates what H. Denis Wu (2000) calls a "discrepancy between the 'real world' and the 'news world' " (pp. 23-4).…”
Section: Introductionmentioning
confidence: 98%
“…This imbalance in the global exchange of news means, in the words of Jaap van Ginneken (1998), "the perspectives of the great mass of the world population are under-represented in global news, while those of relatively small élites are overrepresented" (p. 143). This tendency creates what H. Denis Wu (2000) calls a "discrepancy between the 'real world' and the 'news world' " (pp. 23-4).…”
Section: Introductionmentioning
confidence: 98%
“…Our study opens up two avenues to pursue in future studies. First, it may be worthwhile to apply controls for endogeneity to existing empirical analyses (e.g., Gaddy & Tanjong, 1986;Van Belle, 2000;Wu, 2000;Wu et al, 2002) that employ other units of analysis and different dependent variables. Second, over the years media coverage has evolved; what once was only covered in printed newspapers can now be transmitted almost instantaneously through the Internet.…”
Section: Resultsmentioning
confidence: 99%
“…Although agencies like the Associated Press make news available that other reporting agencies can pick up, this does not allow for the substantive reporting that a news bureau in-country can provide. Wu's (2000) wide-ranging study of news reporting in 38 countries found that the presence of an international news bureau significantly increased the likelihood of coverage (see also Larson, 1979;Wu et al, 2002). This should not be surprising; a news agency must maintain a reputation of reporting accurate events, and in-country news bureaus provide an additional measure of validation regarding an event.…”
Section: Similarity Of Interestsmentioning
confidence: 91%
See 2 more Smart Citations